Completion of the Diffusion Wave Flood Tracking Model Using the Method of Lines (MOL) - Istikomah, Istikomah; Fauzi, Yulian; Nursalim, Rahmat (UNIB Press, 2024)
The flood tracking model is a method that can be used to predict when a flood will occur. The flood wave model is developed using a diffusion equation consisting of mass conservation equations and momentum conservation equations. This research was conducted to determine the application of the Method of Lines (MOL) in solving flood tracking models using the diffusion equation. The steps involved are discretizing the flood wave diffusion tracking equation by replacing the spatial derivative using the central difference method, resulting in a system of ordinary differential equations. Then, solving the system of ordinary differential equations using the fourth-order Runge Kutta method. The approach used in this research is quantitative. Simulations are performed by inputting a sample case and entering the data into the MATLAB program. The flow discharge produced increases as the flow velocity increases, and the resulting graph becomes more concave as the velocity increases. Thus, by knowing the changes in flow velocity, flow width, and flow depth in the upstream area of the river, it can be predicted how much the water discharge will change at each observation point downstream of the river.